Simple heuristics for the assembly line worker assignment and balancing problem - Moreira, Mayron Cesar O.; Ritt, Marcus; Costa, Alysson M.; Chaves, Antonio A. [UNESP] (Springer, 2012)
We propose simple heuristics for the assembly line worker assignment and balancing problem. This problem typically occurs in assembly lines in sheltered work centers for the disabled. Different from the well-known simple assembly line balancing problem, the task execution times vary according to the assigned worker. We develop a constructive heuristic framework based on task and worker priority rules defining the order in which the tasks and workers should be assigned to the workstations. We present a number of such rules and compare their performance across three possible uses: as a stand-alone method, as an initial solution generator for meta-heuristics, and as a decoder for a hybrid genetic algorithm. Our results show that the heuristics are fast, they obtain good results as a stand-alone method and are efficient when used as a initial solution generator or as a solution decoder within more elaborate approaches.
Keywords: Assembly lines; Disabled workers; Heuristic approaches; Hybrid genetic algorithm